Respon Sistem Homeostasis Kalsium Tikus Ovariektomi yang Mengkonsumsi Kombinasi Calcitriol dengan Raloxifene - Hartiningsih Hartiningsih; Devita Anggraeni (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Normal range of calcium (Ca) level in the blood is maintained by Ca homeostasis in the intestinal, kidney and bone. The objective of this research was to study the response of calcium homeostasis system ovariectomized rats consuming combination of calcitriol and raloxifene by calcium balance study. Twenty five female Wistar rats at 8 weeks of age were divided into five groups of five: normal control (NK), ovariectomy control (OVK), ovariectomy+calcitriol (OVD ), ovariectomy+ raloxifene (OVR), and ovariectomy+calcitriol+ 20raloxifene supplementation (OVDR), of five each. Seven weeks after the surgery, each rats was placed into individual metabolic cages for Ca balance studies (Ca consumption, feces and urine Ca excretion, and intestinalCa absorption). In 5 to 8 days of the balance studies, the remaining food, urine, and feces were collected every day for Ca analyses. The results showed that Ca consumption, feces and urine Ca excretion, and intestinal Ca absorption of OVDR rats were higher than OVK rats. Consumption and feces Ca excretion of OVDR rats were higher than OVK rats which informed the decrease of estrogen hormone. Intestinal Ca absorption of OVDR rats was higher than OVK rats which informed the decrease of parathyroid hormone. Meanwhile, urine Ca excretionof OVDR rats was higher than OVK rats which informed the decrease of parathyroid hormone and estrogen. In conclusions, the response of calcium homeostasis system in ovariectomized rats consuming combination ofcalcitriol and raloxifene for 8 weeks was marked by increasing Ca absorption in intestine and Ca excretion in urine.